Indigenous peoples, natural resources and governance agencies and interactions - Tennberg, Monica; Broderstad, Else Grete; Hernes, Hans-Kristian (Routledge research in polar regions., 2022)
This book offers multidisciplinary perspectives on the changing relationships between states, indigenous peoples and industries in the Arctic and beyond. It offers insights from Nordic countries, Canada, Australia, New Zealand and Russia to present different systems of resource governance and practices of managing industry-indigenous peoples' relations in the mining industry, renewable resource development and aquaculture. Chapters cover growing international interest on Arctic natural resources, globalization of extractive industries and increasing land use conflicts. It considers issues such as equity, use of knowledge, development of company practices, conflict-solving measures and the role of indigenous institutions. Focus on Indigenous peoples and Governance triangle Multidisciplinary: political science, legal studies, sociology, administrative studies, Indigenous studies Global approach: Nordic countries, Canada, Russia, Australia, New Zealand and Canada Thorough case studies, rich material, and analysis The book will be of great interest to legal scholars, political scientists, experts in administrative sciences, authorities at different levels (local, regional and nations), experts in human rights and natural resources governance, experts in corporate social governance.